Synthesis and Characterization of Hydrogel Cassava Pulp–Poly (Acrylate – Acrylamide) at Various Concentrations of Acrylic Acid and Crosslinker - Winarti , Christina; Kurniati, Mersi; Puspita, Indah; Suwarda, Rosniyati; Widaningrum; Maddu, Akhiruddin (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Cassava pulp or bagasse is a by-product of cassava processing with high starch and cellulose, showing strong potential for development into various high-value products, including hydrogel. Hydrogel is a polymer capable of absorbing a large amount of water without dissolving and is suitable for several applications. Therefore, this study aimed to synthesize and characterize hydrogel made from cassava waste pulp with different concentrations of acrylamide and acrylic acid (AA). The treatments used were the percentage of acrylic acid, namely 0, 5, 15, 25, and 35%, alongside N, N-methylene bisacrylamide (MBA) percentages (0, 0.5, 1, and 1.5%). Parameters observed were swelling, swelling kinetics, gel fraction, mechanical properties, and surface morphology. The results showed that the addition of acrylic acid and crosslinking with MBA had a significant effect on swelling, gel fraction, and mechanical properties at a significant level of 5%. FTIR confirmed the chemical interaction comprising acrylic-acrylamide acid andMBA in cassava pulp. In line with the analysis, the best treatment was obtained from 25% acrylic acid percentage and 0.5% MBA concentration with 1058% swelling value and 70.05% gel fraction. This hydrogel had a hardness of 6.46 mJ, 5.39 kPa modulus of elasticity, and 4.34 x 1023 m-3 active bonds per unit volume, showing the potential for use in agricultural fields as a planting medium, water carrier, and fertilizer protector.